Reflections on the Situation in Western Armenia in the Pages of “Horizon” on the Eve and at the Beginning of World War I - Karapetyan, Armen (History and Culture, 2026)
On the eve of the First World War, a rather difficult, complex and tense situation had developed in Western Armenia. Although the agreement on reforms had already been signed, the Young Turk authorities not only had no intention of implementing it, but also incited the incitement of anti-Armenian sentiments among the Kurds, Circassians and other Muslim communities. "Horizon", one of the influential Eastern Armenian periodicals published in Tbilisi, kept everything related to the reforms and the Armenian Question in the spotlight. Its pages constantly contained fresh information and analyses on the situation in Western Armenia. The daily strongly condemned the Armenian-displacing and depopulation-oriented practices of the Turkish authorities. Although European inspectors were already in Armenia, they were forced to leave as soon as the First World War began. The reforms again remained on paper: unfeasible.
Keywords: Western Armenia; "Horizon" daily newspaper; Armenian question; reform program; anti-Armenian sentiment; violence; correspondents; practices